THE RELATIONSHIP BETWEEN PARENTAL CONCERN AND INTEREST IN LEARNING ACHIEVEMENT - Jumiati, Eka (EMPATHY Jurnal Fakultas Psikologi, 2013)
Abstract             This research was aimed to determine the relationship between parental concern and interest in learning achievement. Subject in this research were students of class VIII C and VIIID SMP Pangudi Luhur I Yogyakarta. The data analysis technique used is the product moment correlation analysis and multiple regression analysis with data collection tool using a scale and documentation, the result show significant correlation between parental concern and interest in learning achievement. The higher the parental concern and interest in learning the higher the academic achievement obtained. Conversely, the lower the parental concern and interest in learning, the lower achievement obtained. Keywords :parental concern, interest in learning, achievement.